Distribution of plasma cells and other cells containing immunoglobulin in the respiratory tract in chronic bronchitis - Soutar, C. A. (1977)
Soutar, C. A. (1977).Thorax, 32, 387-396. Distribution of plasma cells and other cells containing immunoglobulin in the respiratory tract in chronic bronchitis A study of the distribution of cells containing immunoglobulin in the respiratory tract in chronic bronchitis has been carried out on necropsy tissues from six subjects who died from complications of severe chronic obstructive bronchitis and five subjects with `incidental' chronic bronchitis who died from unrelated disease. The results have been compared with previous reported findings in normal subjects. There was a deficiency of IgA cells in all six subjects with fatal chronic bronchitis when compared with normal subjects. The IgA cell counts in the subjects with `incidental' chronic bronchitis corresponded to normal values for healthy non-smokers and did not share the increased cell counts in lower lobe bronchus occurring in healthy smokers. This work suggests that subjects who die from chronic obstructive bronchitis are deficient in plasma and other cells containing IgA in the respiratory tract, and that subjects with `incidental' chronic bronchitis are normal in this respect. A preliminary study in which local bronchial secretion of IgA was estimated in the sputum of patients with severe chronic obstructive bronchitis showed that bronchial IgA secretion appeared to be low during acute infections in five out of 14 patients. This finding is consistent with the hypothesis that bronchial IgA secretion is impaired in a proportion of patients with severe chronic bronchitis.